1991
DOI: 10.3109/00365519109104563
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular free calcium concentration and thromboxane A2formation of vascular smooth muscle cells are influenced by fish oil and n-3 eicosapentaenoic acid

Abstract: in rat VSMC stimulated by a variety of vasoactive agonist, fish oil and EPA can markedly attenuate intracellular mechanisms related to changes of cytosolic calcium concentration and eicosanoid production.(ABSTRACT TRUNCATED AT 250 WORDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Furthermore, an increase in cellular Ca 2+ is associated with enhanced cell contraction, vasoconstriction and cell proliferation and, thus, may be involved in the development of cardiovascular diseases [35]. Among various biochemical derangements, the increase in intracellular Ca 2+ plays a permissive role in the development of arrhythmia [36] and cardiac hypertrophy [37].…”
Section: Enzymes Regulating Calcium Ion Channelsmentioning
confidence: 99%
“…Furthermore, an increase in cellular Ca 2+ is associated with enhanced cell contraction, vasoconstriction and cell proliferation and, thus, may be involved in the development of cardiovascular diseases [35]. Among various biochemical derangements, the increase in intracellular Ca 2+ plays a permissive role in the development of arrhythmia [36] and cardiac hypertrophy [37].…”
Section: Enzymes Regulating Calcium Ion Channelsmentioning
confidence: 99%
“…Moreover, LDL increases the gene transcription of c‐fos and egr‐1, which are essential transcription factors for VSMC proliferation (3, 64). Locher et al reported that LDL induces generation of thromboxane A 2 (65), a potent growth‐promoting factor for VSMCs (66). Up‐regulation of the Ang II AT1 receptor by LDL has been observed in VSMCs resulting in an elevation of the functional AT1 receptors and a potentiation of the Ang II‐induced DNA synthesis (41).…”
Section: Effects Of Ldl On Vsmc Growthmentioning
confidence: 99%
“…EPA can attenuate elevation of intracellular calcium generation in cultured rat aortic vascular smooth muscle cells (Locher et al, 1991). Elevation of intracellular calcium is a central intracellular signalling system by which hormones and growth factors regulate many different processes such as secretion, metabolism, cell growth, differentiation and cell contractility.…”
Section: Attenuation Of Elevation Of Intracellular Calciummentioning
confidence: 99%